1960
DOI: 10.2134/agronj1960.00021962005200030004x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Male Gametophyte in Dallisgrass Reproduction1

Abstract: Synopsis Pollination is necessary for seed set in common and yellow‐anthered dallisgrass. Although common has a high percentage of aborted pollen, there appears to be enough functional pollen for good seed set. Growth of pollen tubes into the ovule of common and yellow‐anthered dallisgrass is a prerequisite for endosperm formation. Pollination is not essential for embryogenesis in common but is necessary in the yellow‐anthered type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1962
1962
2005
2005

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Information about tube germination and growth is limited for most Paspalum species. WILSON & HOLT (1960) reported that P. dilatatum tubes entered the embryo sac 10 to 12 hours after pollination. Improved microscopy techniques used in this study probably account for the discrepancy between their findings and these.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information about tube germination and growth is limited for most Paspalum species. WILSON & HOLT (1960) reported that P. dilatatum tubes entered the embryo sac 10 to 12 hours after pollination. Improved microscopy techniques used in this study probably account for the discrepancy between their findings and these.…”
Section: Resultsmentioning
confidence: 99%
“…There is limited information in the literature concerning this phenomenon in Paspalum species. WILSON & HOLT (1960), using common and yellow-anthered dallisgrass (Paspalum dilatatum POIR) biotypes, found that the pollen tubes of each biotype were capable of entering the embryo sac of the other biotype, but they failed to cross with one another. They suggested that the barrier to hybridization was the failure of the gametes to unite.…”
Section: Introductionmentioning
confidence: 99%
“…A desert climate, even with ample irrigation, apparently provides inadequate relative humidity, and perhaps excessive temperatures, particularly for optimal seed set by dallisgrass. Wilson and Holt (1960) suggested that pollen tube development could be susceptible to high temperatures and low humidity. Although obligate apomicts, with pollination not required for embryogenesis, common pentaploid and hexaploid biotypes of dallisgrass are pseudogamous (Bashaw and Holt, 1958;Burson et al, 1991), requiring pollination for endosperm development and actual seed set.…”
Section: Discussionmentioning
confidence: 99%